AutoCAD 2022 3D Modeling - Hamad, Munir M. (Mercury Learning & Information, 2021)
New and seasoned users will benefit from this book's step-by-step procedures on creating and modifying 3D models, working with cameras and lights, assigning materials to objects, rendering, and printing. It includes, in both metric and imperial units, 50 "mini-workshops" that complete small projects from concept through actual plotting. Solving all of the workshops will create full projects (architectural and mechanical) from beginning to end, without overlooking any of the basic commands and functions in AutoCAD 2022. The companion CD sets up drawing exercises and projects and shows the book's figures in color.